The Theological Analysis of Eternal Damnation: A Study of the Views of Mulla Sadra and Allameh Tabatabai - Fardin Darabi Meydani; Mohamad shabanpour (حکمت اسرا)
The eternal nature of the human soul and the concept of eternal damnation for disbelievers are crucial theological topics in Islamic thought. This article examines the views of Mulla Sadra and Allameh Tabatabai on these issues. Initially, Mulla Sadra, influenced by Ibn Arabi, believed that eternal damnation was not possible, arguing that divine punishment could not be everlasting due to divine wisdom. He maintained that every being has an inherent purpose, and punishment cannot hinder the attainment of perfection. However, he later revised his position, accepting the possibility of eternal damnation, as human actions can become ingrained character traits (malakah), allowing for everlasting punishment. Conversely, Allameh Tabatabai argues that the specifics of the afterlife cannot be established through rational reasoning and must rely on revelation. He supports the concept of eternal damnation based on Islamic texts, asserting that there is no contradiction among them. Allameh believes that Hell’s punishment will be permanent due to the transformation of human nature and the entrenchment of sins as character traits. This research reveals that both scholars emphasize the existence and immaterial essence of the soul. While Mulla Sadra engages in verse interpretation, Allameh Tabatabai stresses the importance of revelation and the consistency of the texts. The study highlights the differing perspectives of these two thinkers on the matter of eternal damnation.